2009
DOI: 10.1039/b909304d
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional cell culture array using magnetic force-based cell patterning for analysis of invasive capacity of BALB/3T3/v-src

Abstract: A three-dimensional (3D) cell culture system has been fabricated using a magnetic force based cell patterning method, demonstrating a facile approach for the analysis of invasive capacity of BALB/3T3/v-src using an magnetic force and magnetite nanoparticles. The 3D cell patterning was performed using an external magnetic force and a pin holder, which enables the assembly of the magnetically labeled cells on the collagen gel-coated surface as array-like cell patterns, resulting in the development of a 3D in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 33 publications
1
54
0
1
Order By: Relevance
“…It has been shown that the magnetically labelled cells can be targeted easily and patterned precisely using magnetic fields [24,25]. Therefore, the magnetic properties of the labelled cells can be exploited by using magnetic fields to direct the cell seeding for spheroid formation, as suggested recently [27].…”
Section: Spheroid Culturementioning
confidence: 98%
“…It has been shown that the magnetically labelled cells can be targeted easily and patterned precisely using magnetic fields [24,25]. Therefore, the magnetic properties of the labelled cells can be exploited by using magnetic fields to direct the cell seeding for spheroid formation, as suggested recently [27].…”
Section: Spheroid Culturementioning
confidence: 98%
“…Seeking to provide an effective, organized, and practical technique, we have developed a methodology for cell patterning in 3D using magnetic force and magnetite nanoparticles [24][28]. Magnetite nanoparticles embedded in cationic liposomes are used for labeling cells via electrostatic interactions between magnetic cationic liposomes (MCLs) and the target cell membrane [29].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, multicellular spheroids are considered useful in vitro systems for drug screening, including tests of drug metabolism and toxicity, [1][2][3][4][5][6] and for studying tumor metastasis. 7,8) Furthermore, such spheroids have attracted much attention for application in cell-based therapy [9][10][11] and as a building block for the construction of large tissues. 12,13) In a previous study, we demonstrated that spheroid formation greatly prolonged the survival of insulinsecreting NIT-1 cells after transplantation in mice.…”
mentioning
confidence: 99%